If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 6x + -4 Reorder the terms: 4y = -4 + 6x Solving 4y = -4 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = -1 + 1.5x Simplifying y = -1 + 1.5x
| 100-5p=-20+7p | | 127=-11x-71 | | -8(y+1)+1=-8y-6 | | x(31-5-x)=10-3x | | 147=63+6x | | 5x-7=2x+7 | | 10m-17m-25m+21m+m=16 | | -5x+23=32 | | 7(x-1)=5(x-15) | | ln(8x-7)=2 | | 8x+44=100 | | 10x+(16y+6)=180 | | 2z+3z= | | -5(x+4)+6=-3(2x+2)+x | | 4x^2+256=y | | 2(3x-51)-x=10-3x | | 22=-14+2x | | -7h-5=-4-4h | | 4z+9z-2z=10 | | 7(x-2)=(x+3) | | 4x+8=20-7x | | 2y+15=3y-1 | | -90=6(7n-1) | | 23X-2=16X+51 | | 1x(3x-10)=90 | | y=0.5x+6.18 | | 5(x-11-7)=16 | | 5x+2+7x=180 | | 5+18=35 | | x=38+x | | 4p-13p+1p=-150 | | 60=3*2y+3*4 |